Admission to intensive care: A qualitative study of triage and its determinants. (25th October 2018) - Escher, Monica; Cullati, Stéphane; Hudelson, Patricia; Nendaz, Mathieu; Ricou, Bara; Perneger, Thomas; Dayer, Pierre
Abstract : Objective: To examine physicians' decision making and its determinants about admission to intensive care. Data Sources/Study Setting: ICU physicians (n = 12) and internists (n = 12) working in a Swiss tertiary care hospital. Study Design: We conducted in‐depth interviews. Data Collection/Extraction Methods: Interviews were analyzed using an inductive thematic approach. Principal Findings: Admission decisions regarding seriously ill or elderly patients with comorbidities are complex. Nonmedical factors such as ICU beds availability, health care resources on the ward, information about patient preferences, and family behavior determine the decision. Code status and the quality of interaction between physicians are key determinants. The absence of code status or poor documentation of code status discussions makes decisions more difficult and laden emotionally, as physicians feel they are making a life‐death decision. Mutual respect and collaborative decision making facilitate the decision. Tensions arise due to ICU physicians' postponing the decision because of lack of beds, ICU physicians' dismissive attitudes, perceived shortcomings in the other physician's completion of expected tasks, and preconceptions about the other physician. Conclusions: Systematic documentation of code status, and fostering collaboration between ICU physicians and internists would facilitate ICU admission decisions in complex clinical situations.